Depreciation and Reproduction Cost - Young, Allyn A. (Quarterly Journal of Economics, 1927)
Depreciation and Reproduction Cost Allyn A. Young Allyn A. Young Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 41, Issue 2, February 1927, Pages 345–349, https://doi.org/10.2307/1883506 Published: 01 February 1927